RELIGIOUS ORIENTATION OF MUSLIM GIRLS AND YOUNG WOMEN BETWEEN PARTICULARISM AND UNIVERSALISM - Meltem Kulaçatan; Harry Harun Behr (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
The appeal of contemporary radical interpretations for young Muslim women and men poses a new challenge to Islamic theology and education. While attention has been given to the radicalization of young men, Muslim women remain marginalized within academic research. This article discusses gender-sensitive issues concerning radicalization. Based on the results of a pretest-study that inquires the success of ISIS regarding the recruiting of young women, aspects of universalism are approached, as constructions of gender, religion and education are discussed. Here, reconstructions of Islam between ideological, systematic and functional references of religion are taken into account.